THE COMPARISON OF PREDICT-OBSERVE-EXPLAIN (POE) LEARNING MODEL USING EXPERIMENTAL METHODS AND DEMONSTRATION METHODS IN IMPROVING STUDENTS UNDERSTANDING OF PHYSICS CONCEPT IN TEMPERATURE AND HEAT - Arfiani, Yuni (Unnes Science Education Journal, 2017)
Abstract ___________________________________________________________________ This research aims to find out the comparison between of the students physics concept understanding who take the lesson using the Predict-Observe-Explain (POE) models with experiment methods and demonstration methods. This research is a quasi-experimental research design pretest-Post Test Control Group Design. The population in this study was 212 students, then take a sample of 60 students who carried out based on non-random techniques conditional. Samples were taken as many as 60 students divided into two experimental classes. Data collection methods used pretest to obtain data on students’ physics concept understanding before being given treatment and posttest to obtain data on students’ physics concept understanding after being treated. Data obtained were analyzed using Independent Samples T-test. The results showed no difference between the understanding of the students’ physics concept understanding who takes the lesson using the Predict-Observe-Explain (POE)models with experiment methods and the demonstration methods. Based on the increase in the average value of pretest and posttest, obtained an average value of the experiments class is 6.65, while the larger demonstration class is 8.33. This suggests that physics learning using POE models with experiment methods are no better to improve students’ physics concept understanding compared using POE models with demonstration methods.